Fully discrete high-order schemes for hyperbolic conservation law. - Shi, Jian (Cranfield University, 1993)
In this paper we investigate fully discrete high-order accurate solutions for system of hyperbolic conservation laws. Second-, third- and fourth-order high resolution schemes are presented. Performance of the methods is assessed by solving test problems for time-dependent Euler equations of Gas Dynamics in one and two space dimensions. We use exact solutions and experimental data to validate the results.